Disability Hate Crime: Perspectives for Change - Burch, Leah (Routledge Studies in Crime and Society Series, 2024)
Bringing together perspectives from academics, practitioners, campaigners, and activists, this book explores the victimology of disability hate crime (DHC). It is essential reading for those engaged with hate studies, victimology, disability, and vulnerable communities, as well as practitioners and campaigners.